Penal Ordinance No. 35: Concealed Weapon[s], §§ 1-4, in Revised Charter Ordinances and Franchises of the City of Lockport (1909) - (:unkn) unknown (My University, 1909)
No person over the age of 16 years shall have or carry concealed upon his person, in said city, any pistol, revolver, or other firearm without a written license therefor, theretofore issued to him by the chief of police of such city as hereinafter provided. Also provided licensing and registration requirements for concealed carry permits
Keywords: CARRY - CONCEALED